Palaeoslopes of Weichselian sand-bed braided rivers in the Toruń Basin (Poland): results of a palaeohydraulic analysis - Weckwerth, Piotr (Wydawnictwo Naukowe UAM, 2011)
Palaeoslopes of Weichselian sand-bed braided rivers have been reconstructed for two stages of fluvial development in the Toruń Basin. (1) The palaeoslope of the ‘fossil’ fluvial succession (buried under Weichselian tills) was calculated on the basis of the median grain size and the Shields parameter. The hydraulic gradient thus found is comparable with the hydraulic gradient of the present-day river. (2) The second developmental stage of the Toruń Basin (as a apart of the Noteć-Warta ice-marginal valley) took place after deglaciation. The slopes of river terraces are a few times lower than those calculated on the basis of the Shields parameter. The palaeoslope of the then river was estimated on the basis of a constant interdependency between the braidplain width, the channel geometry and the grain size. The river gradient that was thus calculated is similar to the measured terrace slope. Palaeoslope estimates in valleys similar to those in the Toruń Basin should consider the width of the braidplain.
Keywords: Palaeoslope; Shields parameter; Sand-bed braided river; River terraces; Central Poland